A rare heteromorphism of chromosome 20 and reproductive loss. Issue 7 (July 1991) - Romain, D R; Whyte, S; Callen, D F; Eyre, H J
Abstract : A rare centromeric heterochromatic variant of chromosome 20 was encountered during investigations in a couple with repeated miscarriages. The enlarged segment was G and C band positive and stained positively by Giemsa II. In situ hybridisation of the biotinylated alphoid probe D20Z1 specific for the centromere of chromosome 20 to metaphase cells confirmed the presence of amplified sequences adjacent to the centromere. The variant was found to be familial and was evaluated as having no clinical significance.